Features of Filipino infant directed speech (IDS) and maternal input - Rillo, Richard M. (Animo Repository, 2019)
When talking to infants, adults, especially mothers, espouse a particular type of speech known as Infant-directed Speech (IDS) or “babytalk” or “babytalking”, which contains a set of specialized speech with simplified grammatical construction; more repetitive; and more grammatical than adult-directed speech. Specifically, this study reports on the lexical repertoire of Filipino mothers' IDS enriched by the inclusion of code switching as a linguistic strategy in optimizing language development among multilingual Filipino infants. This study has found out that Filipino mothers use as many nouns as verbs in their IDS more than any other lexical categories; and explored inter-sentential code switching as a strategy in their IDS. The findings of this study generate baseline information in part by recent cross-linguistic studies on early lexical development, contrary to the universal noun-bias hypothesis among young children, and the use of a single language in addressing young children to optimize language development. © 2019 Asian E F L Journal Press. All rights reserved.